Level of Real Wages and Labour Productivity in the Manufacturing Sector of the Punjab (The Pakistan Development Review, 1983)
The study analyses the determination of the level of real wages and labour productivity across industries as well as over time in a simultaneous-equation frame work. It has been postulated that an increase in real wages leads to a greater intensity of effort on the part of workers, resulting in higher productivity within a certain range. Higher productivity denotes an improvement in the “ability to pay” and results in payment of higher wages. The study finds that real wages and productivity are significantly related with each other.